2016
DOI: 10.1021/acs.jpcb.6b08622
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field Sensitivity of Storage Modulus for Bimodal Magnetic Elastomers

Abstract: The magnetic-field dependence of the storage modulus for bimodal magnetic elastomers consisting of carbonyl iron with a diameter of 2.8 μm (magnetic) and aluminum hydroxide with a diameter of 1.4 μm (nonmagnetic) was measured, and the effect of nonmagnetic particles on the magnetic-field sensitivity of the storage modulus was investigated. The coefficient of the magnetic-field sensitivity for the monomodal magnetic elastomer increased from 0.018 to 0.026 mT for the bimodal one by embedding nonmagnetic particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…A magnetic gel or elastomer with magnetic particles exhibited a significant increase in storage modulus exceeding 500 times with respect to the off-field modulus [18,19]. Moreover, bimodal magnetic elastomers consisting of both magnetic and nonmagnetic particles demonstrated an enhanced magnetic response due to the chains of magnetic particles associated with nonmagnetic ones [20][21][22][23][24][25][26]. These results indicate that the nonmagnetic particle functions as an intermediator of stress transfer between the chains of magnetic particles although the particles are not moved by magnetic fields.…”
Section: Introductionmentioning
confidence: 92%
“…A magnetic gel or elastomer with magnetic particles exhibited a significant increase in storage modulus exceeding 500 times with respect to the off-field modulus [18,19]. Moreover, bimodal magnetic elastomers consisting of both magnetic and nonmagnetic particles demonstrated an enhanced magnetic response due to the chains of magnetic particles associated with nonmagnetic ones [20][21][22][23][24][25][26]. These results indicate that the nonmagnetic particle functions as an intermediator of stress transfer between the chains of magnetic particles although the particles are not moved by magnetic fields.…”
Section: Introductionmentioning
confidence: 92%
“…The increase in the storage modulus for bimodal magnetic elastomers containing zinc oxide particles of 12 vol.% was 500 kPa, which was achieved by applying a magnetic field of 500 mT, which is 4.2 times that used for the monomodal one (120 kPa) [9]. The increase in the storage modulus for bimodal magnetic elastomers containing aluminum hydroxide particles of 6.6 vol.% was 3.27 MPa, which is 4.3 times that used for the monomodal one (754 kPa) [11]. Figure 1 shows the schematic illustrations representing the mechanism for the MR effect for bimodal magnetic elastomers in our previous study and the scenario for that in the present study.…”
Section: Introductionmentioning
confidence: 98%
“…When a magnetic field is applied to a magnetic elastomer, the elasticity increases due to the chain structure formation (restructuring) of magnetic particles, which is called the magnetorheological (MR) effect. So far, we have investigated the MR effect for polyurethane-based magnetic elastomers and found that bimodal magnetic elastomers with magnetic and nonmagnetic particles exhibit a significant MR effect compared with monomodal magnetic elastomers [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] We have also reported that bimodal magnetic elastomers consisting of magnetic and nonmagnetic particles exhibit the enhanced magneto mechanical response compared to the monomodal magnetic elastomers. [10][11][12][13] Recently, magnetic elastomers attract much attention as damping materials which can control the resonant frequency of vibration by magnetic fields. It is because that the elastic modulus of magnetic elastomer can be changed continuously by magnetic fields.…”
Section: Introductionmentioning
confidence: 99%